Personality - Durand, Robert; Newby, R.; Peggs, L.; Siekierka, M. (Routledge, 2013)
We conduct a clinical study of the investment behavior of 115 subjects. Using Norman’s Big 5, Preference for Innovation and Risk-Taking Propensity (from Jackson’s Personality Inventory), and Bem’s sex-role inventory, we confirm the argument presented in Durand, Newby, and Sanghani [2008] that personality is related to investment choices and outcomes. We extend Durand et al. by demonstrating that investors’ reliance on two heuristics used to model market movements—the availability heuristic and the disposition effect—are associated with their personality traits.